Performance Study of Agricultural Extension Workers at the Agricultural Extension Center (BPP) in Salahutu District, Central Maluku Regency, Maluku Province - Ricard Paratya; Melvis A. Tahitu; Risat a. Far Far (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to determine the performance of agricultural extension workers and factors related to the performance of extension workers. This study used the swot analysis method. The results showed that extension performance succeeded in increasing agricultural productivity, farmer welfare, and the quality of agricultural products with environmental support factors, local governments, communities, and related institutions for agricultural extension performance.